(untitled) (TAMADDUN NURI JURNALI, 2024)
The article talks about the significant role of social conditions and spiritual environment in the formation of the philosophical views of the great thinker Abdurrahman Jami. At the same time, the specific aspects of the spiritual closeness between Alisher Navoi and Jami are explained in detail. While researching the literary and social environment of this period, Orientalist Y. E. Bertels lists important aspects of Navoi.